Strategies to improve writing skills case study: Guisela - Fabre Villón, Leslye Jenyffer (2023)
In the present, the English language is often referred to as "the foreign language," which offers several opportunities in education and the workplace. The educational system has transformed its methodologies to incorporate new didactic strategies that aim to facilitate learning in an efficient, effective, and fluid manner. The present research work, entitled "Strategies to Improve Writing Skills: A Case Study of Guisella Cáceres," aims to demonstrate the use of writing as a pedagogical tool and showcase her proficiency in the foreign language. This research is framed within the context of teaching and learning English as a foreign language......